Pengembangan Model Pembelajaran Matematika Berbasis Flipped Classroom Pada Siswa Kelas XI SMKN 1 Gedangsari Gunungkidul - Damayanti, Herry Novis; , prof. Dr. Sutama, M.Pd; , Dr.Suyatmini,SE.,M.Si (2016)
The aim of the research was developed of mathematic theaching model based Flipped Classroom. The final result of the research is to tasted the effectiveness of mathematic theaching model based Flipped Classroom. The research method is Research and development that includes introduction, field study of theaching management in the school, planning and preparing Flipped Classroom model, implementation of theaching firs cycle, second cycle, and third cycle, and exam of attitude, skill, and learning outcome. The result of the study was mathematic teaching model based Flipped Classroom at the eleven grade student of SMKN 1 Gedangsari Gunungkidul can maximize the time of theaching the classroom by maximizing the direct instruction and interaction one by one through teaching video that was uploaded in online or offline. The teaching material divided into two types, they were teaching video from ck-12.org site and original materials that were made by the students. Mathematic theaching model based Flipped Classroom used Problem Based Learning (PBL) method in the first and second cycle, while in the third cycle used Discovery Learning (DL) method for increasing creativity, responsibility, and skill of study. The effectiveness of the model was used covariance analysis test (ankova). It shows that the level of significant was smaller from 0,05 to 0,00. The effectiveness of the attitude, skill, and learning outcome was used Mann-Whitney non parametric analysis. It shows that level of significant was smaller from 0,005 to 0,003; 0,008; 0,009. The researcher concluded that the implementation of mathematic teaching model based Flipped Classroom at the eleventh grade students of SMKN 1 Gedangsari Gunungkidul was effective.